Functional diversity of soil macrofauna may contribute to microbial community stabilization under drought stress - Morales-Fonseca, Diana; Barantal, Sandra; Buscot, François; Hättenschwiler, Stephan; Milcu, Alexandru; Nahmani, Johanne; Gritti, Emmanuel S.; Goldmann, Kezia; Prada-Salcedo, Luis Daniel (Frontiers in Microbiology, 2025)
The impacts of climate change, particularly the increasing frequency and intensity of severe droughts, pose significant threats to terrestrial ecosystems. To ensure the maintenance of critical ecosystem functions under these conditions, it is essential to better understand the interactions between different soil communities. However, the extent to which drought-induced changes in microbial communities are influenced by soil biodiversity, especially the functional diversity of soil macrofauna, remains poorly understood. In this study, we investigated how microbial communities respond to contrasting levels of macrofauna functional diversity and to more severe and prolonged drought in a Mediterranean forest ecosystem, all under fully controlled conditions. We conducted a two-year mesocosm experiment using 16 large mesocosms at the Montpellier European Ecotron, employing 16S amplicon sequencing and inferred functional gene annotations to assess microbial responses. Our results revealed that the relative abundance of Gram-positive bacterial communities increased compared to Gram-negative ones in response to drought. Furthermore, higher levels of macrofauna functional diversity appeared to help stabilize microbial diversity and community composition during periods of severe and prolonged drought. The resilience of microbial communities to drought was further reflected by the enrichment of drought-tolerant genes in specific bacterial taxa. Overall, these findings highlight the importance of preserving soil biodiversity as a means to mitigate the effects of future droughts on soil functions and to enhance the resilience of terrestrial ecosystems in the face of ongoing climate change.